38. INNOVATIVE USE OF A CUSTOM MOBILE APPLICATION (APP) BY A BRAIN METASTASES PROGRAM FACILITATES MULTIDISCIPLINARY MANAGEMENT OF PATIENTS AND DECREASED LENGTH OF HOSPITAL STAY (LOS). (4th August 2020) - Bovi, Joseph; Lindstedt, Jennifer; Santos-Pinheiro, Fernando; Mueller, Wade; Michael, Straza; Puckett, Lindsay; Thompson, Jonathon; Nelson, Ariel; Peltier, Wendy; Brausch, Carolyn; Erlitz, Tracy; Meerstein, Heather; et al.
Abstract: INTRODUCTION: Patients with Brain Metastases (BM) are complex, mandating multidisciplinary care. Our BM patients are discussed at in-person, weekly Brain Tumor Boards (BTB). However, BM patients diagnosed outside weekly BTBs wait several days for the next BTB, causing delays in generating multidisciplinary plans-of-care, prolonging LOS. We created a custom mobile app for our Brain Metastases Program to have a 'Brain Metastases Virtual Tumor Board' (BMVTB) discussion, in real-time, resulting in faster plans-of-care, decreasing LOS. METHODS: The current pathway for navigating multidisciplinary discussions for patients with BM was examined by members of our Brain Metastases Program. We identified the need for all disciplines to participate in a BMVTB, outside of our in-person, weekly BTB. We developed a secure app that can be downloaded on any provider's mobile device. The app includes a digital BM treatment algorithm for providers to understand comprehensive, data-driven, BM management. The app also gives our multidisciplinary Brain Metastases Program access to a BMVTB messenging tool to securely communicate and generate real-time consensus plans-of-care. Using a Vizient Clinical Database, we retrospectively calculated LOS index (observed LOS/expected LOS) for 184 BM patients over 21 months, creating a baseline. After launching our app and BMVTB workflow we prospectively evaluated LOS index in 45 BM patients over 6 months. RESULTS: Over 21-months, 184 patients demonstrated baseline LOS index of 1.073. After launching our mobile app and BMVTB workflow, 45 patient admissions over 6-months demonstrated LOS index of 0.850. Using Levene's test for equal variances, LOS variance with the app and BMVTB was lower than LOS variance at baseline (p = 0.049). This demonstrates a 38% reduction in LOS when the app and BMVTB generated real-time plans-of-care. CONCLUSION: We demonstrated utility of a custom BM app coupled with a BMVTB to generate real-time plans-of-care for BM patients, reducing LOS.